Promosi Partisipasi Aktif Pada Aktivitas Fisik Bagi Individu Dengan Kondisi Diabetes Melitus Di Puskesmas Setabelan - Devi Rahma Fadila; Farid Rahman; Yusuf Arianto (FKIP, Universitas Palangka Raya, 2023)
Setabelan is one of the sub-districts in Banjarsari District, Surakarta. Based on the recapitulation of disease distribution at the Setabelan Community Health Center during visits in the last 3 months, Diabetes Mellitus was in third place with 205 patients. Diabetes mellitus is a complaint that is often found, especially in the elderly. The outreach program aims to increase public knowledge and understanding regarding the management and prevention of diabetes mellitus through understanding the meaning, risk factors, prevention and management, so as to reduce cases of diabetes mellitus in the community. The method used was education in the form of counseling using leaflets as a medium for the Prolanis group of diabetes mellitus sufferers located at Monument Park 45 Banjarsari. Evaluation of activities uses pre-test and post-test methods to determine the level of understanding and knowledge regarding the material presented. The results show an average pre-test score of 3.80 and an average post-test score of 4.76 with a maximum score of 5.00.